A Folia de Santos Reis: valores e manutenção de costumes - Machado, Claudia Carvalho (2010)
The Folia de Reis is considered a cultural ritual of Brasilian folklore that has suffered the consequences of significant changes occurring today. It becomes essential, from the standpoint of Psychology, the development of studies correlating the Folia with personal values and the meaning of the Folia in different religious groups and participants. This study assumes that the recovery and preservation of immaterial and material heritage is characterized as the very meaning of humanity. 300 people participated in the estudy. The instruments of measurement were: Significance Scale of Folia de Reis adapted Factorial Attitude Scale (Osgood, Suci & Tannembaum, 1957), to measure the sigficance of Folia de Reis and Portrait Questionnaire (Pasquali and Alves, 2004) to assess personal values. For data analysis, descriptive analysis and Anova, with the support of SPSS 14, was used. It was found that the values of pacifism and tradition, peace-and-respect coupled with the positive meaning of Folia de Reis influence in preserving it.